Molecular Microbial Diversity Survey of Sponge Reproductive Stages and Mechanistic Insights into Vertical Transmission of Microbial Symbionts - Schmitt, Susanne (American Society for Microbiology (ASM), 2008)
Many marine sponges, hereafter termed high-microbial-abundance (HMA) sponges, harbor large and complex microbial consortia, including bacteria and archaea, within their mesohyl matrices. To investigate vertical microbial transmission as a strategy to maintain these complex associations, an extensive phylogenetic analysis was carried out with the 16S rRNA gene sequences of reproductive (n = 136) and adult (n = 88) material from five different Caribbean species, as well as all published 16S rRNA gene sequences from sponge offspring (n = 116). The overall microbial diversity, including members of at least 13 bacterial phyla and one archaeal phylum, in sponge reproductive stages is high. In total, 28 vertical-transmission clusters, defined as clusters of phylotypes that are found both in adult sponges and their offspring, were identified. They are distributed among at least 10 bacterial phyla and one archaeal phylum, demonstrating that the complex adult microbial community is collectively transmitted through reproductive stages. Indications of host-species specificity and cospeciation were not observed. Mechanistic insights were provided using a combined electron microscopy and fluorescence in situ hybridization analysis, and an indirect mechanism of vertical transmission via nurse cells is proposed for the oviparous sponge Ectyoplasia ferox. Based on these phylogenetic and mechanistic results, we suggest the following symbiont transmission model: entire microbial consortia are vertically transmitted in sponges. While vertical transmission is clearly present, additional environmental transfer between adult individuals of the same and even different species might obscure possible signals of cospeciation. We propose that associations of HMA sponges with highly sponge-specific microbial communities are maintained by this combination of vertical and horizontal symbiont transmission.